Program Edukasi untuk Peningkatan Keterampilan Administrasi Logistik Unit Food di PT Sekar Bumi Tbk - Igga Oktavia; Kafidin Muzakki (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This service outlines the implementation of an educational program aimed at improving the logistics administration skills of the food unit at PT Sekar Bumi Tbk. Through training needs analysis, comprehensive counseling, and training methods that include theory and practice, this program has succeeded in significantly improving employees' technical and soft skills. The evaluation results show a reduction in errors in managing logistics administration, goods release and goods entry transactions, receiving finished products from the packing team, and following the loading process for local and export shipments. In addition, establishing a culture of collaboration and continuous learning among employees creates an innovative work environment. Thus, this educational program not only strengthens human resource capacity, but also increases the competitiveness of PT Sekar Bumi Tbk in the increasingly competitive frozen food industry, preparing employees to face future challenges more prepared and responsive.